Solitary phytoplankton cells sink in the mesopelagic ocean - Annie Bodel; Margaret Estapa; Colleen A. Durkin (PLoS ONE, 2025)
Phytoplankton, and their carbon, are typically exported from the surface ocean when packaged inside larger, sinking detrital particles. This process draws carbon out of the atmosphere, where it can be sequestered for long time periods in the deep ocean. Phytoplankton can also sink as solitary cells, but direct observations are scarce and the ecological significance is unknown. We collected unprecedented observations of solitary sinking cells during month-long observations in the upper 500 m at two contrasting ocean locations. While these cells account for only a small fraction of the total particulate organic carbon flux (<5%), they provide essential nutrients and a persistent source of food to deep sea ecosystems while preserving a seed bank for future phytoplankton blooms. In one case, observed depth changes over time allowed calculation of a sinking speed of 6 m d -1 . The disaggregation of detrital aggregates collected at the same time could not account for the magnitude or composition of individually sinking cells in our samples, although in some instances their fluxes were correlated. Instead, the data imply that these solitary cells were transferred through the upper mesopelagic as individually sinking particles and play key roles in ocean ecology and biogeochemistry.